Task Force on Design and Analysis in Oral Health Research: Medication-Related Osteonecrosis of the Jaw. (July 2018) - Ruggiero, S.; Saxena, D.; Tetradis, S.; Aghaloo, T.; Ioannidou, E.
Knowledge Transfer Statement : This article discusses the proceedings of the conference organized by the Task Force on Design and Analysis in Oral Health Research on the understanding of the translational evidence on the etiology and pathogenesis of medication-related osteonecrosis of the jaw as well as the clinical protocols on patient management.